Multiple sclerosis : new hope and practical advice for people with MS and their families - Rosner, Louis J., 1929-; Ross, Shelley (New York : Simon & Schuster, 1992)
Authors Rosner and Ross offer a positive approach to understanding and coping with MS in a book that provides up-to-date information in clear, nontechnical language. The book covers diagnosing the disease, its varying symptoms and courses, and dealing with the emotional problems that accompany MS.
Includes index.
Keywords: Multiple sclerosis -- Popular works; Multiple Sclerosis -- Popular Works